2008
DOI: 10.1080/87565640701884253
|View full text |Cite
|
Sign up to set email alerts
|

ADHD Symptoms and Executive Function Impairment: Early Predictors of Later Behavioral Problems

Abstract: This longitudinal study investigated ADHD symptoms and EF impairments in terms of continuity and cross-domain associations, as well as their predictive relations to a range of socioemotional problem behaviors. We applied a factorial ANOVA design to study additive and interactive effects in a sample of non-clinical preschool children (N = 87) and complemented these analyses with group contrasts. The results showed that early ADHD symptoms and EF impairments acted as predictors of continuing problems within each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 54 publications
8
94
0
1
Order By: Relevance
“…This finding confirms previous findings in other studies of early predictors for behavioral problems, which found that externalizing problems 23,24 and attention/hyperactivity problems 25 in childhood predicted later psychosocial problems. Other studies found that problems with enuresis in children were associated with behavioral problems.…”
Section: Discussionsupporting
confidence: 83%
“…This finding confirms previous findings in other studies of early predictors for behavioral problems, which found that externalizing problems 23,24 and attention/hyperactivity problems 25 in childhood predicted later psychosocial problems. Other studies found that problems with enuresis in children were associated with behavioral problems.…”
Section: Discussionsupporting
confidence: 83%
“…Other studies (Barkley, 1998;Brocki et al, 2010;Gambin & Świȩcicka, 2009;Sonuga-Barke et al, 2002;Wåhlstedt et al, 2008) agree that, usually, the ADHD symptoms occur simultaneously with behavioural inhibition. But working memory and flexibility are also affected (Brocki et al, 2010;Re, De Franchis, & Cornoldi, 2010).…”
Section: Palabras Clavementioning
confidence: 72%
“…Some studies have found strong correlation between EF dysfunctions and ADHD symptoms in children (Brocki, Eninger, Thorell, & Bohlin, 2010;Mullane et al, 2011;Sonuga-Barke et al, 2002). Recent studies (Clark, Prior, & Kinsella, 2002;Fischer, Barkley, Smallish, & Fletcher, 2005;Wåhlstedt et al, 2008) have found that ADHD symptoms along with EF impairments are early predictors of continued disruptive behaviour disorders due to features such as inattention, poor impulse control, and poor planning ability.…”
Section: Palabras Clavementioning
confidence: 99%
See 2 more Smart Citations